2021
DOI: 10.2147/ceor.s289459
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Utility Analysis of Anterior Vertebral Body Tethering versus Spinal Fusion in Idiopathic Scoliosis from a US Integrated Healthcare Delivery System Perspective

Abstract: Anterior vertebral body tethering (VBT) is a non-fusion, minimally invasive, growth-modulating procedure with some early positive clinical outcomes reported in pediatric patients with idiopathic scoliosis (IS). VBT offers potential health-related quality of life (HRQoL) benefits over spinal fusion in allowing patients to retain a greater range of motion after surgery. We conducted an early cost-utility analysis (CUA) to compare VBT with fusion as a first-choice surgical treatment for skeletally immature patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 54 publications
0
12
0
1
Order By: Relevance
“…The $50 000 threshold was selected to promote a more conservative analysis, 2,18 while the $100 000 threshold was chosen to align with recommendations from the World Health Organization (WHO) for cost-effectiveness analyses. [38][39][40] One-way deterministic sensitivity analysis (OSA) was performed to assess the outcome sensitivity of individual model parameters. A parameter was considered to be sensitive if a variation of �20% in its value changed the preferred treatment strategy.…”
Section: Variablementioning
confidence: 99%
See 1 more Smart Citation
“…The $50 000 threshold was selected to promote a more conservative analysis, 2,18 while the $100 000 threshold was chosen to align with recommendations from the World Health Organization (WHO) for cost-effectiveness analyses. [38][39][40] One-way deterministic sensitivity analysis (OSA) was performed to assess the outcome sensitivity of individual model parameters. A parameter was considered to be sensitive if a variation of �20% in its value changed the preferred treatment strategy.…”
Section: Variablementioning
confidence: 99%
“…2,18,40,41 Results of OSA were presented using tornado diagrams. 2,40 Probabilistic sensitivity analysis (PSA) modelling of 10 000 microsimulations was conducted as a means to predict the variance and distribution of treatment costs, utilities and ICER in a generalised population setting for both RA-THA and mTHA. 18 Treatment costs and utilities were modelled using gamma distributions, while transition probabilities were modelled using beta distributions.…”
Section: Variablementioning
confidence: 99%
“…If a primary outcome is prespecified, authors should cite a protocol or clinical study publication from which it is derived and justify excluding any other outcomes that were prespecified. Authors are encouraged to describe the nature Example of Item 9: Time horizon 87 "A 15-year time horizon was chosen for the base case of the analysis, beginning with the index procedures. A long-term time horizon (lifetime) was not considered appropriate due to the immaturity of utility data available for the analysis; extensive extrapolation over such a time horizon would be associated with considerable uncertainty.…”
Section: Item 11 Selection Of Outcomes: Describe What Outcomesmentioning
confidence: 99%
“…[18][19][20][21][22] From a cost-utility standpoint, few studies have directly compared the direct costs of AVBT with IPSF. 26 Polly and colleagues found that direct costs were substantially greater for AVBT at $96,897 and $51,351 for IPSF. Our study found higher costs in supplies and OR services for IPSF but similar total direct costs at $50,891 for AVBT and Mean and SDs are provided for continuous variables.…”
Section: Discussionmentioning
confidence: 99%
“…From a cost-utility standpoint, few studies have directly compared the direct costs of AVBT with IPSF 26. Polly and colleagues found that direct costs were substantially greater for AVBT at $96,897 and $51,351 for IPSF.…”
Section: Discussionmentioning
confidence: 99%